2019
DOI: 10.1177/2048004019874989
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular diseases risk factors among adult diabetic patients in eastern Ethiopia

Abstract: Objective The aim of this study was to determine the magnitude of cardiovascular disease risk factors among adult diabetic patients at Hiwot Fana Specialized University Hospital and Jugal Hospital, eastern Ethiopia. Methods An institutional based cross sectional study was conducted on a total of 416 study participants (age ≥18 years) from February to March 2017. Data were collected using: structured questionnaires, measurements of weight, height, and blood pressure, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 12 publications
0
11
1
Order By: Relevance
“…This study revealed that age is the most important risk factor for the development of cardiovascular diseases. Several studies conducted in Ethiopian, and 13 SSA countries and India showed that there is strong relationship between age and cardiovascular diseases [7,21,27,29]. However, this study is inconsistent with the finding from India with the same study design [26].…”
Section: Discussioncontrasting
confidence: 56%
“…This study revealed that age is the most important risk factor for the development of cardiovascular diseases. Several studies conducted in Ethiopian, and 13 SSA countries and India showed that there is strong relationship between age and cardiovascular diseases [7,21,27,29]. However, this study is inconsistent with the finding from India with the same study design [26].…”
Section: Discussioncontrasting
confidence: 56%
“…Dyslipidemia is one of the major modifiable risk factors for CVD in a T2DM patient, which was the leading cause of morbidity and mortality in these patients. 6 Without timely and effective control, the rate of dyslipidemia will continue to rise, leading to a heavy burden of CVD. Therefore, it is important to identify the potential associated factors of dyslipidemia, to manage this condition and reduce the burden of CVD.…”
Section: Discussionmentioning
confidence: 99%
“…5 A study conducted in Ethiopia found that dyslipidemia, physical inactivity, and hypertension were the most common cardiovascular disease risk factors among diabetic patients. 6 In T2DM patients the most common pattern of dyslipidemia was hypertriglyceridemia, reduced HDL cholesterol levels, and an increased concentration of LDL particles. [7][8][9] Dyslipidemia is involved in T2DM due to insulin resistance and increased free fatty acid flux secondary to insulin resistance.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations